Diagnosis of asthma: clinical assessment. Issue 1 (18th March 2015) - Tarasidis, George S.; Wilson, Kevin F.
<x xml:space="preserve">Abstract</x> Background Asthma is a common condition that presents with varied symptomatology and exam findings. The diagnosis of asthma is made through a combination of clinical assessment and diagnostic testing. Methods A literature review was conducted through PubMed, focusing on systematic reviews and practice parameters. The highest‐quality studies and those including the highest number of patients were included. References were reviewed for additional relevant articles. Results Patients with asthma present with the symptoms of cough, dyspnea, and wheezing. The physical exam can demonstrate hyperinflation, wheezing, and increased work of breathing, but most patients will present with a normal pulmonary exam because they are between episodes. The symptoms and examination of patients with asthma varies greatly from patient to patient and within the same patient over time. The diagnosis of asthma in the pediatric population may be more difficult because the classic symptoms may not be present in many of those patients. Conclusion The diagnosis of asthma is made in the setting of clinical history, physical exam, and diagnostic testing. The astute physician will rely on all 3 of these factors when making the diagnosis.